Porous structure and mechanical strength of cement-lime pastes during setting. (November 2015) - Fourmentin, M.; Faure, P.; Gauffinet, S.; Peter, U.; Lesueur, D.; Daviller, D.; Ovarlez, G.; Coussot, P.
Abstract: The acceleration of a cement paste setting as a result of lime addition may be shown from isothermal calorimetry measurements. We investigated the underlying mechanisms through two techniques that provide information on porous structure (using Nuclear Magnetic Resonance) and mechanical properties (elastic modulus measured by rheometry). The correlation of the two sets of results on a cement paste clearly reveals the successive steps of setting, and particularly highlights the so-called induction period. We show that this induction period disappears in the presence of lime, leading to an acceleration of the setting. We also show that beyond some critical concentration of added lime the acceleration of setting is negligible.